The evolution of German Cut Fencing in the 19th century viewed through the works of Friedrich August Wilhelm Ludwig Roux - Alex Kiermayer (Bern Open Publishing, 2020)
This article takes a look at the characteristics of German civilian fencing with cutting swords in the 19th century, especially the style taught by the Roux family of fencing masters. One of the most prominent members of this family was Friedrich August Wilhelm Ludwig Roux. By comparing his early work Anweisung zum Hiebfechten mit graden und krummen Klingen and his later work Deutsches Paukbuch one is able to discern some of the changes in German Hiebfechten or fencing with cutting weapons during the 19th century, in particular on the students' duelling ground. Fencing in 19th century Germany was practiced for a number of different reasons. These included military service, physical education and the civilian duel. A particular form of the civilian duel in Germany was the student's Mensur. The works of the Roux family naturally revolve mostly but not exclusively around this subject as most of them were employed as University fencing masters. In the military and in physical education the contemporary method of the "Berliner Turnschule" was more popular.